Current Management of Femoral Neck Fractures (Literature Review) - Zazirnyi, I.M.; Kostrub , O.O. (TERRA ORTHOPAEDICA, 2021)
Summary. Femoral neck fractures are a commonly encountered injury in orthopedic practice and result in significant morbidity and mortality. It is essential that surgeons are able to recognize specific fracture patterns and patient characteristics that indicate the use of particular implants and methods to effectively manage these injuries. The use of the Garden and Pauwels classification systems has remained the practical mainstay of femoral neck fracture characterization that help choosing appropriate treatment. Operative options include in situ fixation, closed or open reduction and internal fixation, hemiarthroplasty, and total hip arthroplasty. Recent reports demonstrate diversity among orthopedic surgeons in regard to the optimal treatment of femoral neck fractures and changing trends in their management.